Biomechanical study of mid-flight body segment action and its effect on hang-time for volleyball spike jumps - Gupta, D.; Jensen, J.; Abraham, L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study examined pilot data exploring approaches to testing whether the existing explanation about the biomechanics of hang-time in a basketball jump shot proposed by Bishop and Hay (1979) is applicable for spike jumps in volleyball and to identifying possible additional factors that could have an influence on hang-time in volleyball. Kinematics of spike jumps of volleyball players (n=3) using a technique that would theoretically increase hang-time were compared to jumps using a technique that would theoretically decrease it. The results suggested that the mechanisms creating hang-time in volleyball spike jumps are not the same as those in a basketball jump shot. These results suggested that the leg contributions are different and that the motion of the trunk also contributes to hang-time.